Essays on labor economics - FREITAS FILHO, Paulo Roberto de Sousa (2018)
This thesis consists of papers that analyzes different aspects of the labor Market in Brazil, using distinct methods. In the first paper we estimate gender and racial discrimination using data from the 2010 Brazilian Census and the reweighing and recentered influence function regressions proposed by Firpo, Fortin and Lemieux (2009). This method overcomes several limitations of the traditional Oaxaca-Blinder decomposition and improves upon the ones proposed by Machado and Mata (2005) and Melly (2005). For comparison purposes, we also perform the counterfactual analysis proposed by Chernozhukov, Fernández-Val and Melly (2013). The second paper is about migration, a topic that is debated by policymakers in many countries. McKenzie, Gibson and Stillman (2010) estimated the income gains from immigration using data from a random selection of immigrants in New Zealand. They also found evidences that the difference-in-differences (DID) and the bias-adjusted matching estimators perform best among the alternatives to instrumental variables. The DID estimator requires the assumption that the average outcomes for treated and controls follow parallel paths over time to produce reliable results. In this paper we identify the effects of migration on wages of immigrants, using a semi-parametric DID estimator proposed by Athey and Imbens (2006), which allows a systematic variation in the effects of time and treatment across individuals. Finally, Litschig and Morrison (2013) found evidence that intergovernmental transfers cause a reduction in poverty and an increase in per capita schooling and literacy rate. Thus, it is expected that improved educational and social conditions will lead to an increase in migration to municipalities receiving more transfers. The third article analyzes the impact of intergovernmental transfers on immigration in Brazil, using a corrected bias regressor discontinuity design (RKD), proposed by Calonico, Cattaneo and Titiunik (2014), and RAIS/MIGRA immigration data. We find evidence that transfers cause an increase in immigration.